Midazolam and propofol used alone or sequentially for long-term sedation in critically ill, mechanically ventilated patients: a prospective, randomized study - Zhou, Yongfang; Jin, Xiaodong; Kang, Yan; Liang, Guopeng; Liu, Tingting; Deng, Ni (Critical care (London, England), 2014)
Midazolam and propofol used alone for long-term sedation are associated with adverse effects. Sequential use may reduce the adverse effects, and lead to faster recovery, earlier extubation and lower costs. This study evaluates the effects, safety, and cost of midazolam, propofol, and their sequential use for long-term sedation in critically ill mechanically ventilated patients. A total of 135 patients who required mechanical ventilation for >3 days were randomly assigned to receive midazolam (group M), propofol (group P), or sequential use of both (group M-P). In group M-P, midazolam was switched to propofol until the patients passed the spontaneous breathing trial (SBT) safety screen. The primary endpoints included recovery time, extubation time and mechanical ventilation time. The secondary endpoints were pharmaceutical cost, total cost of ICU stay, and recollection to mechanical ventilation-related events. The incidence of agitation following cessation of sedation in group M-P was lower than group M (19.4% versus 48.7%, P = 0.01). The mean percentage of adequate sedation and duration of sedation were similar in the three groups. The recovery time, extubation time and mechanical ventilation time of group M were 58.0 (interquartile range (IQR), 39.0) hours, 45.0 (IQR, 24.5) hours, and 192.0 (IQR, 124.0) hours, respectively; these were significantly longer than the other groups, while they were similar between the other two groups. In the treatment-received analysis, ICU duration was longer in group M than group M-P (P = 0.016). Using an intention-to-treat analysis and a treatment-received analysis, respectively, the pharmaceutical cost of group M-P was lower than group P (P <0.01) and its ICU cost was lower than group M (P <0.01; P = 0.015). The proportion of group M-P with unbearable memory of the uncomfortable events was lower than in group M (11.7% versus 25.0%, P <0.01), while the proportion with no memory was similar (P >0.05). The incidence of hypotension in group M-P was lower than group (P = 0.01). Sequential use of midazolam and propofol was a safe and effective sedation protocol, with higher clinical effectiveness and better cost-benefit ratio than midazolam or propofol used alone, for long-term sedation of critically ill mechanically ventilated patients. Current Controlled Trials ISRCTN01173443. Registered 25 February 2014.